Analisis Biaya Pengobatan Asma Anak Pada Pasien Rawat Jalan di Rumah Sakit Pemerintah di Yogyakarta Berdasarkan Tarif INA-CBG's Tahun 2023 - Ingenida Hadning; Muhammad Aqil Faiq Akbar; Aris Widayati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Asthma is one of the most common chronic respiratory diseases in children, affecting daily activities, growth, and quality of life. Recurrent treatment imposes a considerable economic burden on families and healthcare providers. The Indonesian government implements the Indonesian Case-Based Groups (INA-CBG) payment system within the National Health Insurance (JKN) program to control healthcare costs. Objective: This study aimed to analyse direct medical costs and evaluate the conformity between actual treatment costs and INA-CBG tariffs in 2023 for pediatric outpatient asthma patients at a public hospital in Yogyakarta. Methods: An observational retrospective study was conducted using medical records and cost data of pediatric asthma outpatients at RS Paru Respira Yogyakarta from January 2024 to September 2025. Samples were selected through total sampling based on inclusion and exclusion criteria. Descriptive analysis was used to calculate direct medical costs, while conformity with INA-CBG tariffs was analysed using a one-sample t-test and a Wilcoxon test. Results: A total of 79 patients with 290 outpatient visits were analysed. The average actual costs were Rp248,953 for Q-5-44-0 (n=243), Rp383,490 for J-3-13-0 (n=28), and Rp406,506 for J-3-16-0 (n=19). Medication costs accounted for the largest component (42-52%). Significant differences were found between actual costs and INA-CBG tariffs for all codes (p<0.05). Actual costs exceeded tariffs for codes Q-5-44-0 and J-3-13-0 but were lower for code J-3-16-0. The total negative difference reached Rp14,282,904. Conclusion: There is a significant discrepancy between actual treatment costs and INA-CBG tariffs for pediatric outpatient asthma care in 2023. Medication costs represent the largest component of treatment expenditures. These findings indicate the need for continuous evaluation of the INA-CBG payment system and healthcare cost management strategies to improve efficiency while maintaining service quality.